Metabolism of triacylglycerols in Rhodococcus species: insights from physiology and molecular genetics - Alvarez, Hector Manuel (2013)
Rhodococcus bacteria possess the ability to accumulate variable amounts of triacylglycerols (TAG) during growth on diverse carbon sources. The evolution seems to have selected these microorganisms as specialists in the accumulation of TAG among bacteria, since their biochemistry is efficiently designed for the biosynthesis and mobilization of these lipids. Detailed research of rhodococcal TAG metabolism started only a few years ago; thus, the fundamental understanding of this process and its regulation remains to be clarified. However, some interesting advances in the basic knowledge on TAG metabolism in rhodococci have been made. Most studies have focused on the physiology of TAG biosynthesis and mobilization in rhodococci. Only recently, some advances in molecular biology and genetics on TAG metabolism occurred as a result of the increasing available genomic information and the development of new genetic tools for rhodococci. These studies have been focused principally on some enzymes of TAG biosynthesis, such as the wax esters/diacylglycerolacyltransferases (WS/DGAT) and TAG granule-associated proteins. In this context, the most relevant achievements of basic research in the field have been summarized in this review article.